Review of The Handbook of Economic Sociology - Piore, Michael J. (Journal of Economic Literature, 2016)
T HIS BOOK is a big, ambitious undertaking, organized in 31 long chapters covering subjects which range from religion and civilization in economic life to money, banking, wages, and incentives. But, as the title suggests, it is essentially a research tool. It is meant not so much to be and reviewed as to be The test is whether people end up coming back to it more and more or less and less as time goes on. Judging from those areas of economics and sociology in which I have worked, I would predict people will return to The Handbook of Economic Sociology more and more. The chapter by Chris Tilly and Charles Tilly on labor market structures, the area I know best, is the most comprehensive review of the subject; it handles with rare sophistication, material drawn from across the social sciences. The essay by Alejandro Portes on the informal sector and that by Ivan Light and Stavros Karageorgis on the ethnic economy also consolidate areas of study dispersed over the literature of a variety of different disciplines. But I doubt that any single person is in a well-informed position to pass judgment on all of the essays in the volume. Nonetheless, the publication of a book like this provides an occasion to reflect upon the field of scholarly endeavor, to consider what it represents as a complement to conventional economics and, possibly, as an alternative. For this, it seems reasonable to the text, or at least peruse it, chapter by chapter. The first thing to be said about approaching The Handbook of Economic Sociology in that way is that it is a true handbook: The editors, Neil J. Smelser and Richard Swedberg, provide very little guidance on how it might be read as opposed to referred to. It has no real introduction. It invites readers to pick out chapters at random, following their own inclinations. This, moreover, turns out to be a very frustrating experience. It leaves one wondering what economic sociology is, or even, what economics is that economic sociology is not. Absent some other guide, one seems forced back to basic definitions. In introductory economics-at least when I teach it-we offer two of these. One defines economics broadly as the study of how people employ scarce resources and distribute them over time and among competing demands (Paul Samuelson 1961). The other is much narrower and more focused: